The Triangle of Safety in Business Organizations: A Survey of the Opinions of a Sample Worker in the Nineveh Electricity Distribution Directorate/ Parties - Alnofal, Sultan; Fathi, Sultan (The Arab Journal of Administration, 2021)
A safety is represent of humanist needs that motivated management to importance across of a cornerstone which it (trust, transparency, governance). Trust reflex a positive expectation attitude of workers in organization to agreed of voluntary accept that contributed to avoidance uncertainty to others. Transparency devoted clarity and absenteisim dilemma as well as avoidance of ambiguity and governance centrated with efforts in order to obligated with Behavior rules in framework of social responsibility that objective to interacted with…. Performance and diagnosis risk across of self-control. The problem study fete of question: Do organization of study sample have a cornerstone translate the safety triangle? The hypothesis study is non availability cornerstone to ensurance safety in research organization. that can to achievement of aims the objective of this study declaring of position the triangle of safety in organization research and determine the precedency of this cornerstone and the study applicated of random sample of workers which it involve (44) persons. In order to reach of objectives this study depend on questionniare as a tool of collect data concerned with this subject which it contained (21)items that’s related with cornerstone of safety in organization research. The researchers recruitment many statistical tools such as (frequency, percentage, medium standard derivation, coefficient of variation) as a measurements determine level of answering of sample workers with items that concerned with cornerstone of safety in business organization, the study reached many conclusion such as availability of safety cornerstone in organization research and there are precedency between this cornerstone from trust, transparency and governance as follow. Depending on this conclusions the study preface many recommendation such. 1- Work of devoted trust in many fields and it bases organized the relation and contributed of performance task. 2- Necessity of clarity in work field in order to avoid ambiguity in order to ensurance cohesiveness between workers. 3- Work of reparation rules, procedures and systematic in interactions between workers that draw and determine the behaviors of workers. 4- Organize of dynamic of safety cornerstone in organization research in order to support it.